Inter-examiner repeatability of measuring phorias using three different methods: Neurolens measurement device, the von Graefe method, and prism cover test - Denise Skiadopoulos; Alaina Bandstra; Valerie Kattouf; Corina van de Pol; Vivek Labhishetty; Sumeer Singh (PLoS ONE, 2025)
Objective Heterophoria is routinely measured during a comprehensive ocular examination. The aim of the current study is to compare the inter-examiner repeatability of the Neurolens measurement device (nMD), a commercially available instrument that objectively assesses phoria, to the inter-examiner repeatability of prism alternating cover test and the von Graefe method. Methods 91young adults aged between 18–60 years were enrolled. Two experienced optometrists assessed phoria on each subject using three methods: the von Graefe method (VG), prism alternating cover test (PCT) and nMD. VG and PCT were performed at distance (6m) and near (40 cm). The nMD measurements were obtained using virtual distance (6m) and near (50 cm) targets. All the tests were performed in a single session by both the examiners in a randomized order. Results All study participants were students, staff, and faculty of the Illinois College of Optometry. Of the 91 participants recruited, 65 were female. All participants completed the study with no missing data. The repeatability analysis showed nMD (distance: 0.69 ± 0.77PD; near: 1.00 ± 0.98PD) to have the smallest mean absolute difference at both distance and near compared to VG (distance: 3.28 ± 3.18PD; near: 4.48 ± 3.99PD) and PCT (distance: 1.50 ± 2.36PD; near: 4.05 ± 3.69PD). Bland Altmann analysis showed that the phoria measurements from nMD exhibited significantly less variability when compared with VG and PCT. Conclusions The Neurolens measurement device (nMD) has the highest inter-examiner repeatability when compared to traditional VG and PCT methods. Given that the measurements are objective and repeatable compared to the two traditional methods, this device has the potential to be a useful addition to current methods of clinical practice.